Semi-autonomous drone for agriculture on the tractor base - Kashkarov, Anton; Кашкарьов, Антон Олександрович; Кашкарев, Антон Александрович; Diordiiev, Volodymyr; Діордієв, Володимир Трифонович; Диордиев, Владимир Трифонович; Sabo, Andrii; Сабо, Андрій Георгійович; Сабо, Андрей Георгиевич; Novikov, Hennadii; Новіков, Геннадій Володимирович; Новиков, Геннадий Владимирович (The Journal of Slovak University of Agriculture in Nitra, 2018)
This paper deals with the prospects of using a drone for spraying the gardens and vineyards. Relevance of this process is substantiated with the help of statistical data on the industry in Ukraine. To increase the efficiency of drones during the plant treatment, the concept of a semi-autonomous drone is proposed with connection to a communication line with a tractor – a “tractor-drone” complex. A spraying solution and commands for the drone are transmitted via the communication line. Basic physical formulas for appropriate selection of technical means for the lifting of sprayer frame are presented. Environmental parameters for the flight control system were estimated: temperature fluctuation at 20 K requires screw speed increase by 1.5%; an increase in atmospheric pressure by 5% allows reduction of screw speed by 2%. Tasks of the control system for the concept of semi-autonomous drones are defined in the paper.
Keywords: unmanned aerial system; drone; semi-autonomous; tractor; sprayer; garden